Pengaruh Pandemi Covid-19 Terhadap Minat Penggunaan Mobile Banking Pada Nasabah BNI Syariah Cabang Banda Aceh - Evy Iskandar; Israk Ahmadsyah; Cindy Rahayu (Jurnal Ilmiah Mahasiswa Ekonomi dan Bisnis Islam, 2021)
Mobile banking is a service that provided by banks to make it’s customers easily in transaction at anywhere and anytime. Mobile banking is useful for bank’s customers in carrying out government policies of stay at home and physical distancing to break the chain of virus spread during the COVID-19 pandemic. This study aims to determine the effect of Stay at home and Physical distancing on interest in using mobile banking (Y). during the Covid-19 pandemic. The quantitative method was carried out using multiple linear regression analysis which was processed from 90 respondents from BNI Syariah Banda Aceh customers. The results show that partially and simultaneously stay at home, and physical distancing have a significant positive effect on interest in using mobile banking during the covid-19 pandemic